‘Looking like my favourite Barbie’ – Online Gender Construction of Tween Girls in Estonia and in Sweden - Siibak, Andra; Hernwall, Patrik (Studies of Transition States and Societies, 2011)
The aim of this article is to analyse how tween girls in Estonia and in Sweden describe and discover their gender identities when selecting proﬁ le images for social networking sites (SNSs). To this end, interviews with tweens in Estonia (N=21) and in Sweden (N=31) were carried out. As SNSs largely exist without the recognisable surveillance of adults, children can explore the social matrix of relating to others, and they also feel safe to try out and display diﬀ erent constructions and reconstructions of their identity. At the same time, in communicating online, impression management is formulated with constant worry about how to construct one’s virtual identity so that it will be appreciated and accepted by one’s peer group. In this article, our analysis focuses on the most popular posing strategies used by tween girls, which, it turns out, are often marked by reproduction of the dominant heterosexual cultural norms and values.